STRONGER FORMS OF CONTINUOUS FUNCTIONS VIA sgp-CLOSED SETS IN TOPOLOGY - Bhat, Mahesh (Journal of Global Research in Mathematical Archives(JGRMA), 2017)
The main idea of this paper is to introduce stronger forms of continuous functions such as strongly sgp-continuous, perfectly sgp-continuous and completely sg-continuous functions via sgp-closed sets in topological spaces. Further we also discuss the relation between them by giving counter examples Â Keywords â€”Â set, strongly Â function, perfectly Â function, completely Â function.